2011
DOI: 10.4049/jimmunol.1101235
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 Limits In Vivo Immune Response-Mediated Activation of the IL-12/IFN-γ Pathway, Th1 Polarization, and the Severity of Delayed-Type Hypersensitivity

Abstract: An altered balance between Th1 and Th2 cytokines is responsible for a variety of immuno-inflammatory disorders such as asthma, yet the role of post-transcriptional mechanisms, such as those mediated by microRNAs, in adjusting the relative magnitude and balance of Th cytokine expression have been largely unexplored. Here we show that miR-21 has a central role in setting a balance between Th1 and Th2 responses to antigens. Targeted ablation of miR-21 in mice led to reduced lung eosinophilia after allergen challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
280
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(298 citation statements)
references
References 41 publications
15
280
2
1
Order By: Relevance
“…Il-12p35 mRNA can be targeted by miR-21 in macrophages and DCs, leading to restricted adaptive Th1 responses. [99][100][101] miR-106 has been demonstrated to target Il-10 mRNA, 102 while miR-29 suppresses immune responses against intracellular pathogens by targeting IFN-c. 103 Numerous cytokine encoding mRNAs are regulated by RNA-binding proteins (RBPs) through the AU-rich elements in their 39-UTR, which may play a vital role in mRNA stabilization. MiRNAs can also cooperate with these RBPs to regulate mRNA stability or translation.…”
Section: Mirnas In Regulation Of Tlr and Rig-i Pathways Yk LI And Xy mentioning
confidence: 99%
“…Il-12p35 mRNA can be targeted by miR-21 in macrophages and DCs, leading to restricted adaptive Th1 responses. [99][100][101] miR-106 has been demonstrated to target Il-10 mRNA, 102 while miR-29 suppresses immune responses against intracellular pathogens by targeting IFN-c. 103 Numerous cytokine encoding mRNAs are regulated by RNA-binding proteins (RBPs) through the AU-rich elements in their 39-UTR, which may play a vital role in mRNA stabilization. MiRNAs can also cooperate with these RBPs to regulate mRNA stability or translation.…”
Section: Mirnas In Regulation Of Tlr and Rig-i Pathways Yk LI And Xy mentioning
confidence: 99%
“…Myc activation was associated with gene expression profiling signatures suggesting decreased immune responses and a number of microRNAs overlapped with the molecular Burkitt lymphoma signature, 29,30 including MIR17HG, which was markedly upregulated, and MIR21 (ref. 44) and MIR155HG, which were significantly downregulated. Other studies have shown these microRNAs to be regulated by the Myc, Bcl-6, STAT3, and NF-κB pathways, and the MIR17HG locus was frequently amplified in Burkitt lymphoma.…”
Section: Discussionmentioning
confidence: 94%
“…These researchers further generated miR-21 deficient mice. Compared to wild type mice, in vitro derived moDCs from these mutant mice had enhanced production of IL-12 but not several other cytokines (including TNF-α, IL-6 and IL-23) when they were stimulated with LPS (with or without IFN-γ) (Lu et al, 2011b). In vivo, miR-21 deficient mice also generated a stronger antigen-specific Th1 response, although which DCs contributed to Th polarization in vivo was not clear.…”
Section: Il-12mentioning
confidence: 91%